Preparation method and application of electrolyte for solid oxide fuel cell

The preparation of CeO2 electrolyte through microwave sintering and depositing Pd films on its surface solves the problems of complex preparation and insufficient stability of existing electrolyte materials, and achieves efficient methane oxidation and battery performance improvement.

CN119627163AActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411785336.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In actual application, existing solid oxide fuel cell electrolyte materials face problems such as complex preparation process, insufficient stability and high cost.

Method used

The CeO2 electrolyte was prepared by microwave sintering process, and a Pd film was deposited on its surface by chemical vapor deposition to form an electrolyte with excellent ionic conductivity and catalytic activity.

Benefits of technology

The ionic conductivity and chemical stability of the electrolyte are improved, the service life of the battery is extended, and the catalytic oxidation reaction of methane is promoted through the Pd film, which improves the conversion efficiency of methane and the power density of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of solid oxide fuel cells, in particular to a preparation method of an electrolyte for a solid oxide fuel cell, which comprises the following steps: sintering CeO2; the sintered CeO2 is placed on a sample table in a reaction cavity of CVD equipment, hydrogen and argon are introduced into the reaction cavity, a Pd organic metal precursor enters the reaction cavity in the form of gas after evaporation or sublimation and chemically reacts with the surface of the sintered CeO2 on the sample table, and thus a Pd film is formed through deposition; and thus, the CeO2 solid oxide electrolyte covered with the Pd film on the surface is obtained. The invention also provides an application of the electrolyte, wherein the electrolyte is used for preparing a methane fuel cell. The electrolyte provided by the invention has good ionic conductivity and chemical stability, can maintain stable ion transmission performance in high-temperature and polar environments, and prolongs the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid oxide fuel cells, and in particular to an electrolyte of a solid oxide fuel cell and a preparation method and application thereof. Background Art

[0002] With the continuous growth of global energy demand and the increasingly serious environmental problems, the development of efficient and clean energy technologies has become a global focus. Solid oxide fuel cells (SOFCs) are an efficient and low-pollution energy conversion device that has attracted much attention due to their high energy conversion efficiency, fuel flexibility and environmental friendliness. Methane (CH4), as an important hydrocarbon fuel, has become an important choice for SOFC fuel due to its broad resource base, high energy density and low carbon dioxide emissions. The oxidation reaction of methane in SOFC mainly includes two steps: first, it is partially oxidized under the action of the anode catalyst to produce synthesis gas (H2 and CO), and then hydrogen and carbon dioxide are further produced through the water-gas shift reaction at high temperature.

[0003] The efficient oxidation reaction of methane in SOFC not only depends on the performance of the anode catalyst, but is also closely related to the ionic conductivity and interface properties of the electrolyte. In order to improve the overall performance of SOFC, the electrolyte material needs to have high oxygen ion conductivity and excellent chemical stability in the medium and low temperature range. In order to reduce the operating temperature of SOFC, researchers have proposed a variety of new electrolyte materials, such as Scandia-Stabilized Zirconia (ScSZ), Lanthanum Strontium Magnesium Cobalt Oxide (La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ , referred to as LSGM) and lanthanum nickel oxide (La2NiO 4+δ , referred to as LNO) and so on. These materials show high ionic conductivity in the medium temperature range and have the potential to reduce the operating temperature of SOFC. Zhu et al. from Inner Mongolia University (CN202410560404.X) reported a heterostructured solid electrolyte material composed of CeO2 and β-Al2O3, which can effectively improve the ionic conductivity of the electrolyte, reduce the minimum operating temperature of the fuel cell to 350°C, and improve the electrocatalytic activity of the electrode material. Based on O 2-SOFCs with conductive electrolytes have greater fuel flexibility than low-temperature fuel cells based on proton conductive electrolytes. Bu et al. (CN202410622325.7) reported a Sr / Mg co-doped LaAlO3 electrolyte that improves the working output efficiency of the battery by introducing a large number of oxygen vacancies, thereby achieving the purpose of applying wide-bandgap semiconductors in ion conductors of advanced fuel cells through appropriate element doping.

[0004] However, these new electrolyte materials still face some challenges in practical applications, such as complex preparation process, insufficient stability and high cost. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a preparation method of an electrolyte for a solid oxide fuel cell and a use thereof.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing an electrolyte for a solid oxide fuel cell (i.e., a solid oxide fuel cell using methane as fuel), comprising the following steps:

[0007] 1) Sinter CeO2 (powder) at a set sintering temperature for 2 to 5 hours (to ensure that the CeO2 powder is sintered into a dense solid electrolyte) to obtain sintered CeO2;

[0008] The set sintering temperature is 1200-1500°C;

[0009] Note: CeO2 is evenly spread in a high-temperature crucible, and the crucible is placed in a microwave sintering furnace for sintering;

[0010] 2) Place the sintered CeO2 on a sample stage in a reaction chamber of a CVD device, introduce hydrogen and argon into the reaction chamber, and set the flow rate ratio of hydrogen to argon to 1:(2±0.2); Heat the reaction chamber to 400±20°C, and the Pd organometallic precursor enters the reaction chamber in the form of gas after evaporation or sublimation to react chemically with the surface of the sintered CeO2 on the sample stage, thereby depositing and forming a Pd film;

[0011] The deposition rate of Pd film was controlled to be (0.1±0.01) nm / s;

[0012] The reaction time was set to (1000±100) seconds to achieve a target thickness of (100±10) nm, that is, a CeO2 solid oxide electrolyte with a surface covered with a Pd film with a thickness of (100±10) nm was obtained.

[0013] As an improvement of the preparation method of the electrolyte for solid oxide fuel cell of the present invention:

[0014] The Pd organometallic precursors are Pd(II) acetylacetone and Pd(OAc)2.

[0015] As a further improvement of the method for preparing the electrolyte for solid oxide fuel cells of the present invention:

[0016] The flow rates of hydrogen and argon were set to 100 sccm and (200±20) sccm, respectively.

[0017] As a further improvement of the method for preparing the electrolyte for solid oxide fuel cells of the present invention:

[0018] In step 1), the heating rate is 10±1°C / min, from room temperature to the set sintering temperature.

[0019] The present invention also provides the use of the solid electrolyte prepared by any of the above methods: for preparing methane fuel cells.

[0020] As an improvement of the use of the present invention: the anode, electrolyte and cathode components are assembled together to form a single cell unit of the fuel cell.

[0021] The steps for applying this electrolyte to methane fuel cells are as follows:

[0022] 1) Assemble the anode, electrolyte and cathode components together to form a single cell unit of the fuel cell.

[0023] 2) Connect the methane gas injection system to the anode side and use a gas flow controller to adjust the methane flow rate to 50 sccm. Connect the oxygen or air supply system to the cathode side and use a gas flow controller to adjust the oxygen flow rate to 100 sccm.

[0024] 3) Conduct battery performance testing and analyze the exhaust gas of the methane fuel cell using a gas chromatograph or mass spectrometer.

[0025] The present invention relates to a CeO2 solid oxide electrolyte sintered by microwaves and having a Pd film deposited on the surface, which is an electrolyte for a solid oxide fuel cell using methane as fuel.

[0026] The electrolyte of the present invention has the following advantages:

[0027] 1) CeO2 as an electrolyte has good ionic conductivity and chemical stability, and can maintain stable ion transmission performance under high temperature and polar environment, thus extending the service life of the battery.

[0028] As a catalyst, Pd film can promote the catalytic oxidation reaction of methane gas on the electrolyte surface, thereby improving the methane conversion efficiency and the power density of the battery.

[0029] The present invention combines the microwave sintered CeO2 with the CVD deposited Pd film.

[0030] 2) The optimized microwave sintering process and the surface stability of the Pd film enhance the thermomechanical properties of the electrolyte and reduce the risk of damage caused by thermal shock and material expansion.

[0031] The present invention solves the bottlenecks of existing electrolyte materials in terms of performance and cost through reasonable material design and optimized process flow, and provides strong technical support for the practical application of SOFC.

[0032] In summary, the present invention provides an electrolyte for a solid oxide fuel cell using methane as fuel. Specifically, a CeO2 solid oxide electrolyte is used which is microwave sintered and a Pd film is deposited on the surface. The electrolyte provided by the present invention has good ionic conductivity and chemical stability, can maintain stable ion transport performance under high temperature and polar environment, and prolong the service life of the battery. At the same time, the deposited Pd film can promote the catalytic oxidation reaction of methane gas on the surface of the electrolyte. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0034] Example 1: A method for preparing a CeO2 solid oxide electrolyte with a Pd film deposited on the surface, wherein palladium (II) acetylacetonate is used as a Pd organometallic precursor; the following steps are performed in sequence:

[0035] 1) Evenly spread 10 g of CeO2 powder in a high-temperature crucible, and place the crucible in a microwave sintering furnace; set the temperature program of the microwave sintering furnace to quickly heat it to 1200°C, that is, control the heating rate to be set to 10°C / min, and keep the temperature at 1200°C for 2 hours to ensure that the CeO2 powder is sintered into a dense solid electrolyte, thereby obtaining sintered CeO2.

[0036] 2) Place the sintered CeO2 on a sample stage in a reaction chamber of a chemical vapor deposition (CVD) device, use hydrogen and argon as reaction gases and introduce them into the reaction chamber, set the flow rate ratio of hydrogen to argon to 1:2, and set the flow rates of hydrogen and argon to 100 sccm and 200 sccm respectively. Heat the reaction chamber to 400°C, and acetylacetonate palladium (II) evaporates and enters the reaction chamber in the form of gas to react chemically with the surface of the sintered CeO2 on the sample stage, thereby depositing a Pd film on the surface of the sintered CeO2, and controlling the evaporation rate of acetylacetonate palladium (II) (about 0.0344 mg / s) to control the deposition rate of the Pd film to 0.1 nm / s; the resulting solid oxide electrolyte of CeO2 named as surface-deposited Pd film.

[0037] The reaction time was set to 1000 seconds to achieve a target thickness of 100 nm. That is, a CeO2 solid oxide electrolyte with a surface covered with a Pd film with a thickness of 100 nm was obtained.

[0038] The chemical vapor deposition (CVD) equipment is a conventional device. When the reaction chamber is heated to the set temperature, the Pd organic metal precursor enters the reaction chamber by evaporation or sublimation, and chemically reacts with the CeO2 surface on the sample stage to deposit and form a Pd thin film. The gaseous byproducts (such as methane and water vapor) produced by the decomposition of organic matter, unreacted hydrogen and argon are discharged from the exhaust port.

[0039] The reaction formula is:

[0040] Pd(C5H7O2)2+H2→Pd (deposited on the surface of CeO2)+by-products (such as gaseous hydrocarbons, H2O).

[0041] Note: The function of argon in the reaction gas is to maintain a stable atmosphere under the inertness of the reaction environment, keep the gas composition in the reaction chamber uniform, and promote the uniform deposition of the film.

[0042] Experiment 1: Solid Oxide Fuel Cell Using Methane as Fuel

[0043] The preparation of the solid oxide fuel cell can refer to Example 6 of the disclosed CN118315604A "A button-type solid oxide fuel cell composite anode catalytic electrode based on hydrocarbon fuel reforming technology and its preparation method", but without using a catalytic layer, the NiO-GDC anode functional layer, the solid electrolyte of the present invention and the LSCF-GDC cathode layer are assembled together to form a single cell unit of the fuel cell. Connect the methane gas injection system to the anode side, and use a gas flow controller to adjust the methane flow rate to 50sccm. Connect the oxygen or air supply system to the cathode side, and use a gas flow controller to adjust the oxygen flow rate to 100sccm. Perform a battery performance (power density) test: Use an adjustable current source to gradually increase the current, starting from zero current, and gradually increase to the maximum current of the battery (that is, the voltage drops to near zero). At each current point, measure the corresponding voltage and record the data. With current density (mA / cm 2 ) as the horizontal axis and voltage (V) as the vertical axis to draw a current-voltage (IV) curve. The anode exhaust port of the fuel cell is connected to a gas chromatograph or mass spectrometer for exhaust component analysis. Therefore, a gas chromatograph or mass spectrometer is used to analyze the exhaust gas measured by the anode of the methane fuel cell to calculate the methane conversion rate.

[0044] Power density calculation formula: Power density (W / cm 2 ) = current density (A / cm 2)×Voltage(V)

[0045] Find the point with the highest power density from the IV curve, which is the maximum power density of the battery.

[0046] Methane conversion rate calculation formula: Methane conversion rate (%) = (intake methane flow rate - exhaust methane flow rate) / intake methane flow rate × 100%

[0047] The embodiment 1 was applied to experiment 1, and the performance test results were as follows: the maximum power density was 0.25 W / cm 2 , the methane conversion rate is 95%.

[0048] Experiment 2, stability: Using the battery cell assembled in Experiment 1, run the SOFC battery continuously for 100 hours at a methane flow rate of 50 sccm and an oxygen flow rate of 100 sccm. Continuously monitor and record the output voltage and current of the battery, and calculate the decay rate of the maximum power density of the battery within 100 hours.

[0049] Power density decay rate (% / hour) = (initial maximum power density - power density after 100 hours) / 100 × 100%

[0050] The performance test results are: the power density attenuation rate is 0.10%.

[0051] Experiment 3, thermal mechanical properties test: The expansion coefficient of CeO2 electrolyte at different temperatures was measured using a thermal mechanical analyzer (TMA). The specific operating conditions were: the initial temperature was set at 25°C, the temperature scanning range was set from 25°C to 1000°C, and the temperature was gradually increased at a constant heating rate (10°C / min). At each temperature point, the TMA device will record the length change ΔL of the sample. After heating to the highest temperature, the temperature is gradually reduced at the same rate, and the length change of the sample is recorded.

[0052] The formula for calculating the coefficient of thermal expansion is:

[0053] Wherein, α is the linear thermal expansion coefficient (unit: / °C), ΔL is the length change of the sample (unit: mm), L0 is the initial length (unit: mm), and ΔT is the temperature change (unit: °C).

[0054] Example 1 was applied to Experiment 3, and the test results were as follows: the thermal expansion coefficient was 1.1×10 -6 / ℃.

[0055] Experiment 4, conductivity test: Set the electrochemical workstation to electrochemical impedance spectroscopy (EIS) mode, set the frequency range of EIS measurement to 1 Hz to 1 MHz, the amplitude to 5 mV, collect impedance spectrum data at room temperature, and obtain the resistance value R of the sample by fitting Nyquist or Bode.

[0056] Ionic conductivity calculation formula:

[0057] Where L is the thickness of the electrolyte membrane (100 μm), R is the resistance of the membrane (obtained from EIS data), and A is the contact area between the cathode / anode and the membrane (2 cm 2 ).

[0058] Example 1 was applied to Experiment 4, and the test results were: the ionic conductivity was 4.6×10 -3 / ℃.

[0059] Embodiment 2: Compared with Embodiment 1, the following changes are made:

[0060] The heating temperature in step 1) is changed from "1200° C." to "1500° C.", and the rest is the same as in Example 1.

[0061] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was tested for battery performance according to the above experiment, and the results were as follows: the maximum power density was 0.21W / cm 2 , methane conversion rate is 94%; power density attenuation rate is 0.12% and thermal expansion coefficient is 1.1×10 -6 / ℃, ionic conductivity is 2.5×10 -3 / ℃.

[0062] Embodiment 3: Compared with Embodiment 1, the following changes are made:

[0063] The “keep warm for 2 h” in step 1) is changed to “keep warm for 5 h”, and the rest is the same as in Example 1.

[0064] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.22W / cm 2 , methane conversion rate is 95%; power density attenuation rate is 0.14% and thermal expansion coefficient is 9.0×10 -6 / ℃, ionic conductivity is 3.1×10 -3 / ℃.

[0065] Embodiment 4: With respect to Embodiment 1, the following changes are made:

[0066] The Pd organometallic precursor was changed from "palladium (II) acetylacetonate" to "Pd(OAc)2", and the deposition rate of the Pd film remained unchanged at 0.1 nm / s. The rest was the same as in Example 1.

[0067] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.20W / cm 2 , methane conversion rate is 90%; power density attenuation rate is 0.16% and thermal expansion coefficient is 1.2×10 -5 / ℃, ionic conductivity is 2.5×10 -3 / ℃.

[0068] Comparative Example 1: Compared with Example 1, the following changes were made:

[0069] Cancel step 2), and the rest is the same as Example 1.

[0070] The sintered CeO2 obtained in step 1) was directly used as the electrolyte, and the battery performance test was carried out according to the above experiment. The results obtained were: the maximum power density was 0.10 W / cm 2 , the methane conversion rate is 65%, the power density decay rate is 10.2%, and the ionic conductivity is 3.8×10 -4 / ℃.

[0071] Comparative Example 2: Compared with Example 1, the following changes were made:

[0072] The heating temperature of step 1) is changed from "1200°C" to "1000°C", and "keeping warm for 2h" is changed to "keeping warm for 3h", and the rest is the same as Example 1.

[0073] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.11W / cm 2 , the methane conversion rate is 58%, the power density decay rate is 11.3%, and the ionic conductivity is 4.6×10 -4 / ℃.

[0074] Comparative Example 3-1, relative to Example 1, made the following changes:

[0075] The reaction time was changed from "1000 seconds" to "600 seconds", so the thickness of the obtained Pd film was 60 nm, and the rest was the same as Example 1.

[0076] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.15W / cm 2 , the methane conversion rate is 59%, the power density decay rate is 12.1%, and the ionic conductivity is 4.1×10 -4 / ℃.

[0077] Comparative Example 3-2, relative to Example 1, made the following changes:

[0078] The reaction time was changed from "1000 seconds" to "1500 seconds", so the thickness of the obtained Pd film was 150 nm, and the rest was the same as Example 1.

[0079] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.14W / cm 2 , the methane conversion rate is 67%, the power density decay rate is 9.8%, and the ionic conductivity is 3.1×10 -4 / ℃.

[0080] Comparative Example 4: Compared with Example 1, the following changes were made:

[0081] In step 2), "heat the reaction chamber to 400°C" is changed to "heat the reaction chamber to 100°C". At this time, the deposition rate is about 0.025nm / s, and the reaction time is adjusted accordingly so that the thickness of the Pd film remains unchanged at 100nm; the rest is the same as Example 1.

[0082] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was tested for battery performance according to the above experiment, and the results were as follows: the maximum power density was 0.08W / cm 2 , the methane conversion rate is 40%, the power density decay rate is 8.7%, and the ionic conductivity is 5.5×10 -4 / ℃.

[0083] Comparative Example 5: Compared with Example 1, the following changes are made:

[0084] In step 2), “using hydrogen and argon as reaction gases, with flow rates set to 100 sccm and 200 sccm respectively” is changed to “using hydrogen and argon as reaction gases, with flow rates set to 20 sccm and 200 sccm respectively”, and the rest is the same as in Example 1.

[0085] In this case, due to the decrease in hydrogen partial pressure, the deposition rate of the Pd film is about 0.02nm / s, and the reaction time is adjusted accordingly so that the thickness of the Pd film remains unchanged at 100nm.

[0086] The obtained CeO2 solid oxide electrolyte with Pd film on the surface was subjected to battery performance test according to the above experiment, and the results were as follows: the maximum power density was 0.09W / cm 2 , the methane conversion rate is 41%, the power density decay rate is 8.4%, and the ionic conductivity is 4.5×10 -4 / ℃.

[0087] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing an electrolyte for a solid oxide fuel cell, characterized in that The steps include: 1) Sinter CeO2 at a set sintering temperature for 2 to 5 hours to obtain sintered CeO2; The set sintering temperature is 1200-1500°C; 2) Place the sintered CeO2 on a sample stage in a reaction chamber of a CVD device, introduce hydrogen and argon into the reaction chamber, and set the flow rate ratio of hydrogen to argon to 1:(2±0.2); Heat the reaction chamber to 400±20°C, and allow the Pd organic metal precursor to enter the reaction chamber in the form of gas after evaporation or sublimation to react chemically with the surface of the sintered CeO2 on the sample stage, thereby depositing a Pd film; and obtain an electrolyte for a solid oxide fuel cell; The deposition rate of the Pd film was controlled to be (0.1±0.01) nm / s, and the reaction time was set to (1000±100) seconds.

2. The method for preparing an electrolyte for a solid oxide fuel cell according to claim 1, characterized in that: The Pd organometallic precursors are Pd(II) acetylacetone and Pd(OAc)2.

3. The method for preparing an electrolyte for a solid oxide fuel cell according to claim 2, characterized in that: The flow rates of hydrogen and argon were set to 100 sccm and (200±20) sccm, respectively.

4. The method for preparing an electrolyte for a solid oxide fuel cell according to any one of claims 1 to 3, characterized in that: In step 1), the heating rate is 10±1°C / min, from room temperature to the set sintering temperature.

5. Use of the solid electrolyte prepared by any one of claims 1 to 4, characterized in that: Used to prepare methane fuel cells.

6. The use according to claim 5, characterized in that: The anode, electrolyte and cathode assemblies are assembled together to form a single cell unit of the fuel cell.

Citation Information

Patent Citations

  • Solid electrolyte material and semiconductor ion diaphragm fuel cell thereof

    CN118136903A

  • Preparation method of Sr / Mg co-doped LaAlO3 electrolyte material battery

    CN118231719A

  • Button type solid oxide fuel cell composite anode catalytic electrode based on hydrocarbon fuel reforming technology and preparation method of button type solid oxide fuel cell composite anode catalytic electrode

    CN118315604A

  • Solid oxide fuel cell comprising nanostructure composite cathode and fabrication method thereof

    CN102738495A

  • Methane water vapor reforming catalyst and anode material for solid oxide fuel cell

    CN108110263A